THE MODERATING EFFECT OF LMX QUALITYAND THE MEDIATING ROLE OF TEAM MONITORING ON SHARED LEADERSHIP AND TEAM PERFORMANCE - Zaheer Abbas; Suleman Shah; Syed Usman Shah (Policy Research Journal, 2025)
The aim of this research work is to examine the impact of Shared leadership in teams:The moderating effect of LMX qualityand intermediating role of Team Monitoring, on perceived team performance. The current discussion is based on the LMX theory. In this discussion we have discussed shared leadersip and its impact on team performance such that how shared leadership increases or decrease the team performance. The team performance can be increase through continues monitoring. The shared leadership while studying the theory was suppose to moderate the relation through LMX quality. But while analysis it was found that it does not moderate the relationship. In total 384 responses were collected out of which 356 were validaded. The data was collect through, convenience sampling technique using the Google forms and emails as due to pandemic access to organization was restricted. The data was analyzed using SPSS in which demographics were measured. In order to test the realibility of the data, data set was analyzed through convergent validity in which outer loading of the construct were checked .Construct Reliability/Validity and Discriminant Validity were tested through Fornell-Larcker Criterion and Heterotrait-Monotrait Ratio (HTMT). The findings of the study suggested that there is positive and significant relationship between Shared Leadership and Team performance. Team monitoring capability meditates between shared leadership and Team performance. However from the 356 responses it was found that Leader member exchange quality don’t moderates the relationship between SL and TP and hypothesis was rejected. The particle implication of shared leadership in particle context was learned as shared leadership always increases the performance of any organization. It always improves with proper monitoring and it was concluded that Team performance can be increased with Shared leadership and continuous monitoring.